2022
DOI: 10.3390/molecules27154960
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Dynamics of Human ALKBH2 Dioxygenase in the Course of DNA Repair as Revealed by Stopped-Flow Fluorescence Spectroscopy

Abstract: Elucidation of physicochemical mechanisms of enzymatic processes is one of the main tasks of modern biology. High efficiency and selectivity of enzymatic catalysis are mostly ensured by conformational dynamics of enzymes and substrates. Here, we applied a stopped-flow kinetic analysis based on fluorescent spectroscopy to investigate mechanisms of conformational transformations during the removal of alkylated bases from DNA by ALKBH2, a human homolog of Escherichia coli AlkB dioxygenase. This enzyme protects ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…Dissociation constants were in a narrow range of 2.1-2.7 µM for the binding to the m 1 A-containing DNA and 2.5-4.2 µM for the binding to the m 3 C-containing DNA (Figure 8). It should be mentioned that these values are in good agreement with data obtained previously in an equilibrium fluorescent titration assay [41].…”
Section: Equilibrium Binding Of Wt Abh2 or Its Mutant Forms To Methyl...supporting
confidence: 91%
See 1 more Smart Citation
“…Dissociation constants were in a narrow range of 2.1-2.7 µM for the binding to the m 1 A-containing DNA and 2.5-4.2 µM for the binding to the m 3 C-containing DNA (Figure 8). It should be mentioned that these values are in good agreement with data obtained previously in an equilibrium fluorescent titration assay [41].…”
Section: Equilibrium Binding Of Wt Abh2 or Its Mutant Forms To Methyl...supporting
confidence: 91%
“…It has also been shown that Glu175 and Phe124 contribute to nucleotide-base-specific selection and stabilization in the active site for repair. To elucidate the mechanism of the substrate specificity of the ABH2 enzyme, analyses of conformational changes occurring in the enzyme-substrate complex during the catalytic cycle have been performed by quantum mechanical/molecular mechanical (QM/MM) modeling [39,40] and by the stopped-flow fluorescence spectroscopy technique [41]. The results indicate that the conformational flexibility of protein domains and of the DNA substrate is important for their effective interaction.…”
Section: Introductionmentioning
confidence: 99%
“…This analysis yielded the observed rate constants for demethylation, k obs , which were found to be 0.70 ± 0.08 min −1 and 0.17 ± 0.02 min −1 for the wt and Y143F, respectively. Previously, under identical conditions, the k obs values for another human dioxygenase, ALKBH2, were determined to be 0.22 min −1 for a similar m3C-containing substrate [7]. This difference in rate constants suggests that ALKBH3 exhibits a higher specificity for m3C damage compared to its homologue ALKBH2.…”
Section: Enzymatic Activity Of the Wild-type And Mutant Alkbh3 Proteinsmentioning
confidence: 97%
“…For example, NMR, time-resolved fluorescence spectroscopy, and circular dichroism (CD) have demonstrated a dynamic behavior of AlkB conformation that accompanies the binding of cofactors and a DNA substrate [21,22]. Using a stopped-flow (SF) approach combined with fluorescence spectroscopy we previously demonstrated how the conformational dynamics of AlkB and ALKBH2 proteins induce and follow the recognition and processing of the alkylated substrate [7,23]. The present work was performed by using biochemical and biophysical approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation